Water purification and biological efficacy of green synthesized Co/Zn-Doped α-Fe2O3 nanoparticles - Kumar, Pankaj; Kumar, Sunil; Tapwal, Ashwani; Nimesh, Surendra; Thakur, Naveen (Sustainable Chemistry for the Environment, 2024)
In the present study, Co/Zn doped α-Fe2O3 (Hematite) nanoparticles (NPs) were synthesized using polyvinylpyrrolidone (PVP) and Azadirachta indica (AI) leaves aqueous extract. The analytical techniques including XRD, UV, SEM, EDX, VSM, Raman, and FTIR, we were able to identify and characterize the structural, morphological and magnetic attributes of the synthesized NPs. The findings demonstrated that the synthesized NPs exhibit homogeneous spherical shapes with particle sizes ranging from 8.64 to 15.32 nm. The NPs have rhombohedral crystal lattices, with crystallite sizes of 23.25 nm for chemically synthesized doped α-Fe2O3 NPs and 12.52 nm for those synthesized using green methods. The magnetic study has shown that the saturation magnetization (Ms) value of NPs, which ranges from 36 to 45 emu/g at ambient temperature, exhibits superparamagnetic properties (300 K). The treatment of industrial wastewater and its reuse for agricultural purposes are the subjects of the current study. Different concentrations of doped α-Fe2O3 NPs were used as photocatalysts to degrade dyes in a bioreactor under UV light in a heterogeneous mixture. The degradation rates achieved were 96.42 % for Congo Red (CR) and 98.36 % for Eosin Yellow (EY). DPPH assays were conducted to evaluate the antioxidant activity of the synthesized doped α-Fe2O3 NPs. The percentage inhibition of DPPH radicals ranged from 71.13 % to 90.35 %. Our findings indicate that AI leaf extract holds promise as a valuable resource for the development of bioactive compounds and environmentally friendly approaches to synthesizing green NPs. This is primarily attributed to the increased accessibility of bioactive components with potent antioxidant properties. The combination of these benefits provides opportunities for novel uses in environmental cleanup, biological applications, and energy conversion. [Display omitted]